ENCAPSULATION OF FACTOR IX-ENGINEERED MESENCHYMAL STEM CELLS IN ALGINATE-BASED MICROCAPSULES FOR ENHANCED VIABILITY AND FUNCTIONALITY - Sayyar, Bahareh (My University, 2013)
The work presented in this thesis was focused on design and construction of novel cell-loaded microcapsules by incorporation of bioactive molecules (proteins or peptides) for potential application in hemophilia B treatment. The objective of this study was to improve the viability and functionality of the encapsulated cells by creating biomimetic microenvironments for cells that more closely mimic their physiological extracellular matrix (ECM) environment.
Three cell-adhesive molecules were used in this work: fibrinogen and fibronectin, two abundant proteins present in ECM, and arginine-glycine-aspartic acid (RGD) tri-peptide, the minimal essential cell adhesion peptide sequence and the most widely studied peptide for cell adhesion. Alginate, the most commonly used biomaterial used for cell encapsulation, was combined with either of these molecules to create biomimetic microcapsules. Non-modified alginate (control) and modified alginate matrices were used to encapsulate the factor IX (FIX) secreting cells for protein delivery. In this work, FIX-engineered cord blood-derived human mesenchymal stem cells CB MSCs were used as a cell source for FIX delivery.
Our data suggested that fibrinogen-alginate, fibronectin-alginate and RGD-alginate microcapsules improved the viability of encapsulated MSC and are applicable in cell therapy technologies. However, fibrinogen-alginate and fibronectin-alginate microcapsules more significantly enhanced the proliferation and protein secretion from the encapsulated cells and may have potential for FIX delivery for hemophilia B and other inherited or acquired protein deficiencies. RGD-alginate microcapsules can v potentially be used for other tissue engineering applications with the aim of enhanced viability and attachment of the enclosed cells. Differentiation studies showed the osteogenic (but not chondrogenic or adipogenic) differentiation capability of FIX-engineered CB MSCs and their efficient FIX secretion while encapsulated in fibrinogen-alginate and fibronectin-alginate microcapsules.
Keywords: cell encapsulation; alginate; biomimetic microcapsules; mesenchymal stem cells; hemophilia B; Biomaterials; Biomaterials